2014
DOI: 10.1007/s12013-014-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium

Abstract: With good osseointegration properties, micro-arc oxidation has now gradually become the key point in basic research and clinical trials, but interface between the implant surface treated by micro-arc oxidation and gingival soft tissues has been seldom reported. The influences of micro-arc oxidation surface treatment on the biological behavior of primary human gingival epithelial cells (hGEC) and common pathogen Streptococcus mutans have been studied. MTT method was taken to test the adhesion and growth of hGEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Therefore the presence of anatase in the cpTi surface may be the driven force toward reduction of F. nucleatum adhesion in the MAO group. How-ever, such trend was not observed for mature biofilm, corroborating with previous studies that evaluated the development of other microorganisms in MAO-treated surfaces [69,70]. We believe that the catalytic effect of anatase in the MAO group interfered with F. nucleatum growth in the early biofilm; however during the biofilm development, the growth with the other two species might have protected the bacterium against the catalytic effect.…”
Section: Colony Forming Unitssupporting
confidence: 89%
“…Therefore the presence of anatase in the cpTi surface may be the driven force toward reduction of F. nucleatum adhesion in the MAO group. How-ever, such trend was not observed for mature biofilm, corroborating with previous studies that evaluated the development of other microorganisms in MAO-treated surfaces [69,70]. We believe that the catalytic effect of anatase in the MAO group interfered with F. nucleatum growth in the early biofilm; however during the biofilm development, the growth with the other two species might have protected the bacterium against the catalytic effect.…”
Section: Colony Forming Unitssupporting
confidence: 89%
“…When MCs were released from the nanomicelles, they entered the bacterial cells and inhibited bacterial protein synthesis [ 44 ]. In this study, we observed that MAO-treated titanium significantly promoted the adhesion and proliferation of S. aureus, which concurs with the findings of a previous study [ 45 ]. However, in another study, the authors reported that MAO-treated titanium could only partly restrain bacteria adhesion and growth [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…There are some studies in the literature about CoCrMo alloys manufactured by SLM (Chen et al , 2017; Darvish et al , 2016; Monroy et al , 2015; Qian et al , 2015) for dental applications. However, studies on the different amounts of Streptococcus mutans (S.mutans) between CoCrMo alloys manufactured by SLM and by casting are lacking, yet this information is very important for dental applications (Lv et al , 2014). S.mutans is one of the most common oral bacteria type, and the adhesion of S.mutans to the metal implants mainly depends on the surface roughness (Shahal et al , 1998), surface composition (García, 2005) and corrosion resistance (Zhang et al , 2016).…”
Section: Introductionmentioning
confidence: 99%